2022
DOI: 10.1021/acs.nanolett.1c04116
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation of Interfacial Electronic Properties Induces Friction Tuning under an Electric Field

Abstract: Mysteries about the origin of friction have remained for centuries. Especially, how friction is tuned by an electric field is still unclear. Present tuning mechanisms mainly focus on the atomic configurations and electrostatic force, yet the role of interfacial electronic properties is not fully understood. Here, we investigate a unique friction tuning effect induced by an electric current in a conductive atomic force microscopy experiment and uncover two main tuning mechanisms of friction by the fluctuation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…Owing to its two-dimensional (2D) planar structure with strong in-plane covalent bonding, graphene has an ultrahigh mechanical strength and intrinsically low surface friction. Moreover, it has been shown that the frictional properties of graphene can be actively altered by introducing topological defects, chemical functionalization, varying the supporting substrates, changing the ambient conditions like humidity and temperature, and the electronic method. These unique characteristics render graphene a promising candidate as a versatile friction modifier with atomically thin thickness. Despite the high potential, the friction regulation methods for graphene are typically irreversible, which means that its frictional property is hard to be recovered once changed.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its two-dimensional (2D) planar structure with strong in-plane covalent bonding, graphene has an ultrahigh mechanical strength and intrinsically low surface friction. Moreover, it has been shown that the frictional properties of graphene can be actively altered by introducing topological defects, chemical functionalization, varying the supporting substrates, changing the ambient conditions like humidity and temperature, and the electronic method. These unique characteristics render graphene a promising candidate as a versatile friction modifier with atomically thin thickness. Despite the high potential, the friction regulation methods for graphene are typically irreversible, which means that its frictional property is hard to be recovered once changed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the potential difference (electric field) between the conductive tip and sample has little effect on the friction force (frictional coefficient) here (Figure S2). , The (vertical) contact force discussed in this article mainly refers to the tip–sample interaction force perpendicular to the sample surface.…”
Section: Resultsmentioning
confidence: 99%
“…The friction tuning by external electric field or electric current has been experimentally observed for decades, but the microscopic mechanism still remains elusive. Recently, Song et al [935] revealed the tuning effect of electronic properties fluctuation (EPF), i.e., the electric field-induced electron redistribution and current-induced electron transfer fluctuations, on friction (Fig. 77(c)), based on which a friction model considering the effect of electronic properties fluctuation on potential energy corrugation during friction was proposed.…”
Section: Fundamentals Of Solid Friction and Wearmentioning
confidence: 99%
“…Fig 77. Mechanism of friction and wear at atomistic scale[931,934,935,937]. Reproduced with permission from Ref [931],.…”
mentioning
confidence: 99%
See 1 more Smart Citation